Sustainability risk management: an integrative framework to evaluate emerging risks and other non-quantifiable risks affecting company survival - Abdul Manab, Norlida; Abdul Aziz, Nazliatul Aniza; Md. Jadi, Diara (Inderscience Enterprises Ltd., 2020)
The importance of sustainability risk management (SRM) in managing emerging risks and other non-quantifiable risks has recently been the subject in many discussions. The debate focuses on the flaws of the risk management programme, which excluded sustainability risk in the risk assessment. Thus, this study attempts to develop an SRM framework for company survival by adopting the triangulation approach which integrates both quantitative and qualitative methods to identify the key components of an SRM framework. A total of 88 respondents from public listed companies participated in the survey and four companies were interviewed. The findings highlight that stakeholders' expectations, board and senior management risk oversights, resources and capabilities, risk assessments and methods, and risk reporting are the key factors in developing an SRM framework. As a general conclusion, this study develops a generic SRM framework which is applicable to all types of companies, irrespective of its size or business type.